Under Vilh. Becks prædikestol - Trock, Carl (Kirkehistoriske Samlinger, 1993)
As the dominant personality in the awakening movement called the “Kirkelig Forening for Indre Mission”, Vilhelm Beck (1829-1901) was one of the most important religious leaders in 19th Century Denmark. He encouraged newly awakened Christians to retain their membership of the national church while at the same time antagonizing many contemporaries by his emphasis on clearly ascertainable conversion, followed by a holy life, and on the separate dignity of the converted (“the holy ones”) inside the Church. Most of what has been written about Beck comes from the pens of professional theologians; hence the special interest of the letters brought to light in this article, conveying, as they do, an impression of his impact on two sympathetically critical lay people whose parish pastor he was. P.G.H. Trock, lessee of Kragerup Manor, Zealand, and his wife Margrethe, in their more than one hundred letters to their children, writen during the period from 1880 to 1883, reveal somewhat mixed feelings about Beck and his movement: they admired him and counted themselves among his friends and adherents while at the same time being repelled by the coarseness of his simplifications as well as by the intolerance and one-sidedness of his local followers.